The relationship between occupational noise exposure and hypertension using nearest age-matching method in South Korea male workers. Issue 1 (1st January 2021) - Kim, Min Gi; Ahn, Yeon-Soon
Abstract: There is no consensus as to whether exposure to noise causes HTN. The objective of this study was to investigate the relationships between occupational noise exposure, pre- HyperTensioN (HTN) and HTN. The study subjects consisted of 107, 407 workers who underwent annual special medical check-ups for workers from 2000 to 2004. The control group was an annual medical check-up cohort consisting of 152, 790 workers examined over the same time period. The 1:1 nearest age matching of the two groups was done and multivariable logistic regressions were used to evaluate the effects of occupational noise on pre-HTN and HTN. The adjusted odds ratio (OR) of pre-HTN (OR 1.29, 95% CI 1.27–1.32) in noise-exposed workers was significantly higher than that in non-noised exposed workers. The adjusted OR of HTN (OR 1.42, 95% CI 1.38–1.45) in noise-exposed workers was significantly higher than that in non-noised exposed workers. According to this study, occupational noise exposure might be related to pre HTN and HTN.